ANALYSIS OF INDONESIAN AGRICULTURAL TRADE PERFORMANCE TO BRICS - Zuhdi, Fadhlan; Maulana, Achmad Subchiandi; Tambarta, Emmia; Nurhayati, Nurhayati; Asshagab, Sri Milawati; Rambe, Khoiru Rizqy; Destiarni, Resti Prastika (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The BRICS alliance has become a significant player in the global economy, making it imperative for member nations to engage in strategic trade. With abundant natural resources and a thriving agriculture industry, Indonesia is well-positioned to capitalize on the trade prospects within BRICS. This study utilizes quantitative methods from secondary data. It employs analytical tools, including Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD), and Intra-Industry Trade (IIT), to offer insights and evidence-based recommendations for shaping Indonesia's future trade policies on agricultural commodities within the BRICS framework. The results show that Indonesia's trade in agricultural products with the BRICS countries is positive, as it offers a high level of competitiveness during the period studied. The RCA analysis results show that Indonesian agricultural products are competitive in BRICS. This analysis also shows that India and China have the most significant impact on Indonesian agricultural trade with BRICS. Based on the EPD calculation results, Indonesian agricultural exports to BRICS countries are in the Rising Star quadrant. Based on the analysis, Indonesia's trade in agricultural products with BRICS countries shows a high level of integration with a value of 70.12, indicating significant similarities in the products exchanged.